Neurotoxicity New Advances - Sabuncuoglu, Suna (IntechOpen, 2022)
Neurotoxins are natural or chemical compounds that can disturb the neurological system of mammals. The neurotoxic potential of a neurotoxin is a consequence that may occur if tissue concentrations surpass a particular threshold. Chemicals disrupt adult brain function by interfering with the structure and function of various neuronal pathways, circuits, and systems in diverse ways. Neurotoxicity - New Advances provides updated information about neurotoxicity and neurotoxic chemicals including nanomaterials and pesticides. It also discusses prevention and treatment strategies. This book is an instructive and valuable guide to understanding neurotoxicity and identifying neurotoxicity mechanisms and neurotoxic disorders.